1994
DOI: 10.1002/oti.6150010403
|View full text |Cite
|
Sign up to set email alerts
|

Oral sensorimotor therapy: Assessment, efficacy and future directions

Abstract: This review addresses the current state of knowledge in oral sensorimotor therapy for children with neurological impairments and ingestive problems. Comprehensive assessment of the child with dysphagia looks at the interaction of oral performance and growth. These domains include eating efficiency, oral‐motor skills, oral sensory evaluation, classification of the severity of an eating problem, interaction of respiration and ingestion, aspiration, positioning for feeding, social skills assessment, careload and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…[13][14][15] There have been three reviews documenting measures of OPD in the neonatal age group. 6,12,16 Other authors have explored assessment of OPD in children with CP; 13,17 however, these reviews were not systematic. Hence, our aim was to conduct a systematic review investigating OPD measures for preschool children with CP or neurodevelopmental disabilities.…”
mentioning
confidence: 99%
“…[13][14][15] There have been three reviews documenting measures of OPD in the neonatal age group. 6,12,16 Other authors have explored assessment of OPD in children with CP; 13,17 however, these reviews were not systematic. Hence, our aim was to conduct a systematic review investigating OPD measures for preschool children with CP or neurodevelopmental disabilities.…”
mentioning
confidence: 99%
“…Casaer et al [11] showed that postural controls are present in the neonate, but that they vary with behavioral state and positioning and seem to be task specific, i.e., they change with feeding. Our heightened awareness of the role of postural support/control has evolved from our studies on the efficacy of oral motor therapies in children with CP and eating impairments [12][13][14][15][16][17]. In this domain, it has become clear that the safety of ingestion is dependent on proper positioning of the head, neck, and trunk [18,19].…”
mentioning
confidence: 99%